330. RANDOMIZED PHASE II STUDY OF DOCETAXEL VERSUS PACLITAXEL IN PATIENTS WITH ESOPHAGEAL SCC REFRACTORY TO FLUOROPYRIMIDINE- AND PLATINUM-BASED CHEMOTHERAPY: OGSG1201. (24th September 2022) - Matsuyama, Jin; Yamamoto, Sachiko; Kii, Takayuki; Hara, Hiroki; Kawabata, Ryohei; Kawada, Junji; Takeno, Atsushi; Ueda, Shugo; Kawakami, Hisato; Okita, Yoshihiro; Endo, Shunji; Kimura, Yutaka; et al.
Abstract: There is no standard chemotherapy for esophageal squamous cell carcinoma (ESCC) refractory to first-line fluoropyrimidine- and platinum-based chemotherapy. We therefore performed a randomized, selection-design phase II trial to compare docetaxel (DTX) and paclitaxel (PTX) in this setting. Eligible patients were randomly assigned to receive either DTX (70 mg/m2 on day 1 of each 21-day cycle) or PTX (100 mg/m2 on days 1, 8, 15, 22, 29, and 36 of each 49-day cycle). The primary end point was overall survival (OS), and secondary end points included progression-free survival (PFS), time to treatment failure (TTF), response rate (RR), and safety. Seventy-eight eligible patients (N = 39 in each group) were included for efficacy analysis. The median OS was significantly longer in the PTX group (8.8 vs. 7.3 months; hazard ratio [HR], 0.62; P = 0.047). A significant benefit of PTX over DTX was also apparent in the median PFS (4.4 vs. 2.1 months; HR, 0.49; P = 0.002) and median TTF (3.8 vs. 2.1 months; HR, 0.45; P < 0.001). RR (25.6% vs. 7.7%, P = 0.065) were higher in the PTX group. Neutropenia (80% vs. 28%) and leukopenia (76% vs. 28%) of grade 3 as well as febrile neutropenia (46% vs. 0%, P < 0.0001) occurred more frequently in the DTX group. PTX showed a significantly better efficacy as well as a more manageable toxicity compared with DTX.